Hepatitis B core‐related antigen serum levels are associated with significant liver fibrosis in treatment‐naive chronic HBV infection patients. Issue 6 (8th April 2022) - Liu, Ruyu; Li, Minghui; Lu, Yao; Zhang, Lu; Shen, Ge; Wu, Shuling; Chang, Min; Hao, Hongxiao; Hu, Leiping; Gao, Yuanjiao; Xu, Mengjiao; Xie, Yao
Abstract: Several hepatitis B virus (HBV) serum markers have been identified as risk factors for liver fibrosis in patients with chronic HBV infection, and several noninvasive fibrosis tests based on serum indexes are now used to identify the severity of liver fibrosis. We aimed to identify the relationship between hepatitis B core‐related antigen (HBcrAg) serum levels and liver fibrosis in treatment‐naive chronic HBV infection patients. A total of 246 treatment‐naive chronic HBV infection patients were enrolled in this study. All of the patients underwent liver biopsies at baseline. Using the METAVIR fibrosis stages, there were 15, 140, 50, 26 and 15 patients in the F0, F1, F2, F3 and F4 stages (METAVIR scoring system), respectively. The biochemical, serological and virological parameters were measured using standard laboratory procedures. The HBcrAg serum levels of the patients were examined via ELISA. HBcrAg serum levels of F2, F3 and F4 stage patients were significantly higher than those of nonsignificant liver fibrosis patients (METAVIR F0‐F1), but there were no significant differences among F2, F3 and F4 stage patients. Serum HBcrAg (OR, 2.18; 95% confidence interval [CI], 1.51–3.16), albumin (ALB) (OR, 0.60; 95% CI, 0.41–0.87), prothrombin activity (PTA) (OR, 0.58; 95% CI, 0.40–0.83) and platelet (PLT) counts (OR, 0.38; 95% CI, 0.25–0.57) were associated with significant liver fibrosis (METAVIR F2‐F4). The serum HBcrAg value enabled the correct identification of patients with significant fibrosis, with an area under the receiver operating characteristic curve of 0.81 (95% CI, 0.75–0.88). The APRI, FIB‐4 index and ALBI score can identify significant liver fibrosis with an area under the ROC curve of 0.74 (95% CI, 0.66–0.81), 0.73 (95% CI, 0.65–0.80) and 0.63 (95% CI, 0.55–0.72), respectively. Compared with these three indexes, the accuracy rate of diagnosis of significant fibrosis based on HBcrAg was higher than that of the FIB‐4 index ( p  = 0.0479) and ALBI score ( p  = 0.0030). HBcrAg, ALB, PTA serum levels and PLT counts were associated with significant liver fibrosis in treatment‐naive chronic HBV infection patients. HBcrAg serum levels enabled the correct identification of patients with significant fibrosis (METAVIR F2–F4), and HBcrAg was more effective than the FIB‐4 index and ALBI score.